PENGARUH KUALITAS PRODUK TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN LCGC TOYOTA AGYA - Erin Trisilia Windiyanti (Jurnal Manajerial, 2017)
This research to determine how much influence the performance, features, reliability, and durability to the satisfaction and loyalty. The population in this research is that all customers who buy Toyota Agya at PT. Arina Parama Jaya (Arina Motor) and used Toyota Agya cars for at least one month. The number of samples is 50 samples were selected by using the method of Non-Probability Sampling, namely purposive sampling, and incidental sampling. The data in this research is primary data obtained from questionnaires distributed to respondents. Data were analyzed using logistic regression were processed with SPSS data processing applications 16. Testing was done by using path analysis. The results of hypothesis testing using t-test is known that the performance effect on satisfaction of a count of 13,565 > t table 2.0106, features affect the satisfaction of a count equal to 4.151 > 2.0106, reliability affects the satisfaction of a count equal to 4.5535 > 2.0106, resistance affects the satisfaction of a count equal to 2.403 > 2.0106, effect on customer loyalty satisfaction of the results count equal to 4.116 > 2.0106.